2021
DOI: 10.1101/2021.09.13.459947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated molecular analysis identifies a conserved pericyte gene signature in zebrafish

Abstract: Pericytes reside in capillary beds where they share a basement membrane with endothelial cells and regulate their function. However, little is known about embryonic pericyte development, in part, due to lack of specific molecular markers and genetic tools. Here, we applied single cell RNA-sequencing (scRNA-seq) of platelet derived growth factor beta (pdgfrb)-positive cells to molecularly characterize pericytes in zebrafish larvae. scRNA-seq revealed zebrafish cells expressing mouse pericyte gene orthologs whil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…2c) 30,31 . Further analysis of the mural cells demonstrated enriched transcripts for known pericyte and vascular smooth muscle cell markers, including tropomyosin 1 (tpm1), notch receptor 3 (notch3), regulator of G protein signaling 5a (rgs5a), myosin heavy chain 11a (myh11a), actin alpha 2 smooth muscle (acta2), transgelin (tagln), ATP-binding cassette sub-family C member 9 (abcc9), and chemokine C-X-C motif ligand 12b (cxcl12b), as well as two recently identified mural cell markers NDUFA4 mitochondrial complex associated like 2a (ndufa4l2a) and potassium voltage-gated channel Iskrelated family member 4 (kcne4) 32,33 (Supplementary Fig. 2c).…”
Section: Scrna-seq Reveals Distinct Epicardial Subsetsmentioning
confidence: 99%
“…2c) 30,31 . Further analysis of the mural cells demonstrated enriched transcripts for known pericyte and vascular smooth muscle cell markers, including tropomyosin 1 (tpm1), notch receptor 3 (notch3), regulator of G protein signaling 5a (rgs5a), myosin heavy chain 11a (myh11a), actin alpha 2 smooth muscle (acta2), transgelin (tagln), ATP-binding cassette sub-family C member 9 (abcc9), and chemokine C-X-C motif ligand 12b (cxcl12b), as well as two recently identified mural cell markers NDUFA4 mitochondrial complex associated like 2a (ndufa4l2a) and potassium voltage-gated channel Iskrelated family member 4 (kcne4) 32,33 (Supplementary Fig. 2c).…”
Section: Scrna-seq Reveals Distinct Epicardial Subsetsmentioning
confidence: 99%
“…Besides these contaminating clusters, cluster 6 was identified as mural cells expressing platelet-derived growth factor receptor beta pdgfrb (Figure 2C) 29, 30 . Further analysis of the mural cells demonstrated enriched transcripts for known pericyte and vascular smooth muscle cell markers, including tropomyosin 1 ( tpm1 ), notch receptor 3 ( notch3 ), regulator of G protein signaling 5a ( rgs5a ), myosin heavy chain 11a ( myh11a ), actin alpha 2 smooth muscle ( acta2 ), transgelin ( tagln ), ATP-binding cassette sub-family C member 9 ( abcc9 ), and chemokine C-X-C motif ligand 12b ( cxcl12b ), as well as two recently identified mural cell markers NDUFA4 mitochondrial complex associated like 2a ( ndufa4l2a ) and potassium voltage-gated channel Isk-related family member 4 ( kcne4 ) 31, 32 (Figure S2C). While ndufa4l2a is restricted to a subset of mural cells, kcne4 is highly expressed in mural cells and also present in the core epicardial clusters at lower levels.…”
Section: Resultsmentioning
confidence: 99%
“…and Shih et al (21,37). Briefly, both publications included lists of highly expressed genes identified in all cell type.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, using publicly available data from Shih et al (37), we downloaded the highly expressed genes identified in all pdgfrb-expressing cells (from Supplemental Table S2.1). As described in the publication we filtered for expression level log2>1, this list of genes was defined (which was not certified by peer review) is the author/funder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation